Analysis of historical events using sediment cores and nuclear methods: a case study at a deep basin at North Aegean Sea. - Tasiopoulou, Anastasia; Tsabaris, Christos; Androulakaki, Effrosyni; Manta, Kyriaki; Patiris, Dionisis; Diakaki, Maria (HNPS Advances in Nuclear Physics, 2026)
In this work, a sediment core was collected from the Athos deep basin, in order to assess the natural and anthropogenic radioactivity using a high-purity germanium detector. The activity concentration was determined for the radionuclides 214Pb, 210Pb, 214Bi, 228Ac, 208Tl, and 212Pb, the natural radioisotope 40K and the artificial radionuclide 137Cs, using the gamma spectroscopy method. The sedimentation rate was determined by applying radio-dating models, utilizing both the 210Pbex method (CF:CS model) and the 137Cs method, in order to validate the results. According to the 210Pbex radiometric dating model, the sedimentation rate in the range of 0-8.25 cm is approximately (0.10 ± 0.01) cm/y, while using the 137Cs method, the sedimentation rate is (0.081 ± 0.002) cm/y from the sampling period till the Chernobyl accident and (0.127 ± 0.001) cm/y for the nuclear tests, respectively. The results suggest a relatively high sedimentation rate, with approximately 1 cm of sediment accumulating every 10 years. It appears that the sedimentation rate in this deep basin is influenced by multiple factors, due to land-sea interaction processes as well as due to atmospheric fallout.